Psilocybin: From Serendipity to Credibility? - Rucker, James J.; Young, Allan H. (Frontiers in Psychiatry, 2021)
Psilocybin has a long history of non-medical use and some seem to infer from this that it has therapeutic utility. Early phase clinical trials with psilocybin are encouraging, but suggest only that larger, multicentre trials are required. These are ongoing but will take many years to complete. Meanwhile, retreat centers offering paid experiences with psilocybin truffles have opened in some countries, often using early phase clinical trial data as a basis for bold, public facing claims. This seems unwise. Early phase trials are not designed for their results to be generalized outside the setting they were undertaken in. To do so risks being misleading. Providing what may be seen as an unregulated drug intervention as a paid service is difficult to reconcile with long-held ethical principles underpinning human research and treatment development that were laid down by the 1947 Nuremberg Code and the 1962 Kefauver Harris Amendments. By using psilocybin before it has been properly tested, retreat centers may be undermining their own credibility and the credibility of the wider field.